Confounding the Mighty: Stories of Church, Social Class and Solidarity - Larner, Luke (Hymns Ancient & Modern, 2023)
Intro -- Copyright information -- Contents -- Contributor Biographies -- Foreword -- Prelude -- Section 1: 'The Almighty has done great things for me': Intersectional Experiences of Class and the Church -- 1. Feckless Faith: Why the Relationship between Class and Christian Faith is a Justice Issue -- 2. Wandering in the Wilderness: Education, Class and Dislocation -- 3. Caste, Class and Colour: The Church's Triangle of Tragedy -- Section 2: 'Lifting up the lowly': Class and Leadership in Mission and Ministry -- 4. Consider Your Own Call: Working-Class Vocations in the Church of England -- 5. Resisting Coloniality: Class, Pentecostalism and Contemporary Leadership in the Church in England -- Section 3: 'Casting down the mighty from their thrones': Class, Solidarity and the Struggle for the Common Good -- 6. 'Bullshit Jobs': The Church and the Precariat -- 7. Recovering the Radical: Lessons of Class Solidarity through a Case Study from the Iona Community -- 8. Class in the Classroom: Social Class and Theological Education -- 9. Conclusion: The Spirit and Struggling for Solidarity -- Afterword.